Calcium-phosphate homeostasis in secondary progressive multiple sclerosis patients during mitoxantrone therapy. (2nd December 2021) - Lis, Martyna; Niedziela, Natalia; Nowak-Kiczmer, Maria; Kubicka-Bączyk, Katarzyna; Adamczyk-Sowa, Monika
ABSTRACT: Objectives: To assess calcium-phosphate parameters in SPMS patients treated with mitoxantrone (MTX). Methods: Thirty eight SPMS patients eligible for MTX therapy in the Department of Neurology in Zabrze, Poland were enrolled in a prospective study from March 2016 to November 2019. The parameters of serum calcium-phosphate metabolism and the neurological status according to the Expanded Disability Status Scale (EDSS) were assessed. In patients with hypovitaminosis D, vitamin D (VitD) supplementation was introduced (4000 IU/day for 1 month and later 2000 IU /day). Results: Most patients were women [57.89%]. The mean age [years] was 56.11 (±7.74). The median time from diagnosis to inclusion day (ID) was 7.50 [4.00–14.00] [years]. Due to VitD supplementation, an increase in serum VitD was observed during the study. 84.21% of patients presented with hypovitaminosis D before MTX treatment compared to 47.37% after treatment. Before MTX therapy, none of the patients underwent surgical repair of the fracture compared to 42.11% of patients after MTX treatment (p < 0.01). Discussion: Deficiency of VitD was observed at the baseline in most SPMS patients eligible for MTX therapy. Due to adverse reactions to MTX treatment, this therapy requires patient compliance, cautious drug administration and monitoring during the therapy.